Combining torrefaction pretreatment and co-pyrolysis to upgrade biochar derived from bio-oil distillation residue and walnut shell. (1st November 2019) - Zhu, Xiefei; Luo, Zejun; Diao, Rui; Zhu, Xifeng
Highlights: Torrefaction combined with co-pyrolysis could effectively increase biochar yield. The positive synergistic effects on solid yield were found both in torrefaction and co-pyrolysis. There were opposite synergistic effects on H/Ceff of torrefied feedstocks and biochar. Torrefaction didn't change the infrared absorption peak type of torrefied feedstocks. Torrefaction contributed to the conversion of large aromatic rings in biochar to small aromatic rings. Abstract: In this study, torrefaction combined with co-pyrolysis was proposed to produce biochar from walnut shell and bio-oil distillation residue in a tube furnace. The effect of torrefaction and co-pyrolysis on the yield and properties of biochar was investigated in the torrefaction-pyrolysis process including the evaluation of the properties and yield of torrefied feedstocks. The results showed that the positive synergistic effect between walnut shell and distillation residue on the yield of torrefied blends was found in the torrefaction stage, while the torrefaction had a negative synergistic effect on the hydrogen to carbon atom effective ratio of torrefied blends. The torrefied walnut shell and the torrefied distillation residue had most of the same infrared absorption peaks, and torrefaction did not change the type of infrared absorption peaks of torrefied feedstocks. Furthermore, the positive synergistic effect on the yield and the hydrogen to carbon atom effective ratio of biochar from the blends was confirmed to exist in the co-pyrolysis stage. However, the combined effect of torrefaction and co-pyrolysis had a positive effect on the yield of walnut shell biochar, and had a negative effect on the yield of distillation residue biochar. In addition, torrefaction pretreatment was beneficial to the evolution of large aromatic rings in biochar to small aromatic rings and the formation of ordered carbon.